2013
DOI: 10.1021/ma400039p
|View full text |Cite
|
Sign up to set email alerts
|

Directed Self-Assembly of Block Copolymers into Twin BCC-Sphere: Phase Transition Process from Aligned Hex-Cylinder to BCC-Sphere Induced by a Temperature Jump between the Two Equilibrium Phases

Abstract: We explored in situ a "directed" self-assembly of block copolymers into a twinned body-centered cubic sphere (bcc-sphere) with a special orientation via the order−order phase transition from a specially aligned hexagonal cylinder (hex-cyl) by using time-resolved synchrotron small-angle X-ray scattering and transmission electron microscopy. We elucidated that the hex-cyl with its cylinder axis and {11} lattice plane aligned respectively parallel to the OX axis and the OXZ plane was epitaxially transformed into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
(98 reference statements)
1
17
0
Order By: Relevance
“…Whereas cylinders are almost as well studied as lamellas, the S microstructure in copolymers is rather common only in experimental systems, where it can be obtained either by orderdisorder transition (ODT) 56 or order-order transition (OOT). 57 Its identification by SCFT, 13 in Monte Carlo 19,20 and even DPD 25,41 simulations is usually difficult, if not impossible because of the long equilibration time. Figure 5 reports on the least ordered structures with illdefined peaks on the S(q) dependence.…”
Section: Structure Analysismentioning
confidence: 99%
“…Whereas cylinders are almost as well studied as lamellas, the S microstructure in copolymers is rather common only in experimental systems, where it can be obtained either by orderdisorder transition (ODT) 56 or order-order transition (OOT). 57 Its identification by SCFT, 13 in Monte Carlo 19,20 and even DPD 25,41 simulations is usually difficult, if not impossible because of the long equilibration time. Figure 5 reports on the least ordered structures with illdefined peaks on the S(q) dependence.…”
Section: Structure Analysismentioning
confidence: 99%
“…For block copolymers with bulk BCC structures, many theoretical and experimental studies have been focused on the order-order and order-disorder transitions induced by the substrate and confinement in thin films. 14,[19][20][21][22][23][24] Moreover, ordering of the spheres along the direction normal to the substrate in thin films of asymmetric diblock copolymers with relatively larger layer thicknesses was reported, 25 while the spheres were almost short-range ordered in the plane parallel to the substrate. 26 However, the lateral order and ordering range of the BCC spheres as well as the morphologies at the boundaries of the adjacent ordered domains in thin films of asymmetrical BCP with a thickness within a certain range are rarely investigated.…”
Section: Introductionmentioning
confidence: 98%
“…It is known that the stability of different equilibrium domain morphologies of a block copolymer depends on the relationship between enthalpy (interaction energies between dissimilar polymer blocks given by the Flory-Huggins interaction parameter, χ) and entropy (conformational energy χ and f, the volumetric fraction of one of the co-monomers. Numerous studies have showed various types of equilibrium morphologies of di-blocks AB and tri-blocks ABA copolymers, which are spheres (S), cylinders (C), lamellas (L) and gyroids (G) [45][46][47] . When f is near 0.5, lamellar morphologies are usually expected after annealing during several days.…”
Section: Structural Characterizationmentioning
confidence: 99%